The Terraced Walls Significantly Influence the Spatial Distribution of Soil Water in Terraced Areas on the Loess Plateau - BAI Chenyun; YU Xiaoling; MA Chenchen; HAN Xiaoyang; QIAO Jiangbo; ZHU Yuanjun (Shuitu Baochi Xuebao)
[Objective] Converting slopes into terraces is a crucial soil and water conservation and agricultural measure on the Loess Plateau. Understanding the impact of terraced walls on soil water is conducive to preserving soil water and enhancing terrace productivity. [Methods] Soil samples were collected from different locations on typical artificial high-slope terraces (terraced wall height of 5 meters) on the Loess Plateau to measure soil water content and soil physical and chemical properties. The spatial distribution characteristics and influencing factors of soil water were analyzed. [Results] The results showed that as the distance from the terraced wall increased, the soil water storage in the 0-300 cm soil layer increased significantly from 15.9 mm to 328.6 mm. The evaporation from the terraced wall decreased gradually from 318.0 mm to 83.4 mm. When the terrace width was 300 cm, the evaporation from the terraced wall could account for 33% to 38% of the soil water storage. The depth of the soil layer and the distance from the terraced wall were the main factors influencing soil water content, while the correlation between soil particle composition as well as organic matter content and soil water content was low. [Conclusion] Lateral evaporation caused by the terraced walls on the Loess Plateau significantly affects the distribution of soil moisture, leading to a reduction in soil water on the side adjacent to the walls. Appropriate measures should be taken in terrace maintenance and management to reduce soil water loss due to evaporation from the terraced walls.